2021
DOI: 10.7759/cureus.13652
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anatomic Landmark to Target the Left Ventricle During Chest Compressions in Cardiac Arrest

Abstract: Background Resuscitation guidelines recommend that chest compressions be performed over the lower sternum. Current computed tomography and magnetic resonance imaging studies suggest that the current area of compression does not target the left ventricle (LV). Using transthoracic ultrasound, we sought to identify potential anatomic landmarks that would result in compressions over the LV in the majority of our study participants. Methodology We recruited 64 healthy men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although there is insufficient evidence in the literature to adjust the inter-nipple line for the EAD position, we assumed that the inter-nipple should move slightly downward with the EAD position compared to the IAR position. Thus, the majority of the study group would have the inter-nipple line located within the lower half of the sternum during EAD and would therefore correspond with the current guideline 12 , 19 . Using the inter-nipple line to determine proper hand position may be more comprehensible to the general public in contrast to the ambiguous lower half of the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is insufficient evidence in the literature to adjust the inter-nipple line for the EAD position, we assumed that the inter-nipple should move slightly downward with the EAD position compared to the IAR position. Thus, the majority of the study group would have the inter-nipple line located within the lower half of the sternum during EAD and would therefore correspond with the current guideline 12 , 19 . Using the inter-nipple line to determine proper hand position may be more comprehensible to the general public in contrast to the ambiguous lower half of the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…Though developed to measure bladder volumes, bladder scanners have previously been studied as a potential screening tool to detect abdominal aortic aneurysms with evidence of moderate performance [ 21 , 22 ]. While a recent study showed the LV is most often located along the left sternal border at the 6th intercostal space (ICS), considerable variability persists with LV location ranging from the 3rd to 7th ICS [ 23 ]. Bladder scanners have also been shown to reliably localize the heart in healthy volunteers, with largest scan volumes being most often associated with the area over the long axis of the LV [ 25 ].…”
Section: Introductionmentioning
confidence: 99%